Interpreting foreign policy: National, comparative and regional studies. (September 2015) - Bevir, Mark; Daddow, Oliver
This Special Issue advances an interpretive research programme into Foreign Policy Analysis (FPA) and International Relations by showcasing new work on the study of foreign policy and regional cooperation. This introductory article explains the rationale and contents of the Special Issue in three parts. The opening part explains how the contributions complement the broader study of ideas in FPA and International Relations through a critique of methodological positivism in the social sciences. The second part elaborates the theoretical framework used to cohere the collection, which centres on the study of 'situated agents' who, when confronted with policy dilemmas, draw on inherited traditions to inform their foreign policy practices. This is accompanied by a methods case study centring on David Cameron's European Union referendum strategy, which is used to illustrate the practical ways in which one can conduct interpretivist research into foreign policy. In conclusion, we spell out how the contributors conducted their work to advance the interpretivist research programme.